Differences in Vital Signs Between Elderly and Nonelderly Patients Prior to Ward Cardiac Arrest. Issue 4 (April 2015) - Churpek, Matthew M.; Yuen, Trevor C.; Winslow, Christopher; Hall, Jesse; Edelson, Dana P.
<x xml:space="preserve">Abstract</x> Objectives: Vital signs and composite scores, such as the Modified Early Warning Score, are used to identify high-risk ward patients and trigger rapid response teams. Although age-related vital sign changes are known to occur, little is known about the differences in vital signs between elderly and nonelderly patients prior to ward cardiac arrest. We aimed to compare the accuracy of vital signs for detecting cardiac arrest between elderly and nonelderly patients. Design: Observational cohort study. Setting: Five hospitals in the United States. Patients: A total of 269, 956 patient admissions to the wards with documented age, including 422 index ward cardiac arrests. Interventions: None. Measurements and Main Results: Patient characteristics and vital signs prior to cardiac arrest were compared between elderly (age, 65 yr or older) and nonelderly (age, < 65 yr) patients. The area under the receiver operating characteristic curve for vital signs and the Modified Early Warning Score were also compared. Elderly patients had a higher cardiac arrest rate (2.2 vs 1.0 per 1, 000 ward admissions; p < 0.001) and in-hospital mortality (2.9% vs 0.7%; p < 0.001) than nonelderly patients. Within 4 hours of cardiac arrest, elderly patients had significantly lower mean heart rate (88 vs 99 beats/min; p < 0.001), diastolic blood pressure (60 vs 66 mm Hg; p = 0.007), shock index (0.82 vs 0.93; p < 0.001), and Modified Early Warning Score (2.6 vs 3.3; p < 0.001) and higher pulse pressure index (0.45 vs 0.41; p < 0.001) and temperature (36.4°C vs 36.3°C; p = 0.047). The area under the receiver operating characteristic curves for all vital signs and the Modified Early Warning Score were higher for nonelderly patients than elderly patients (Modified Early Warning Score area under the receiver operating characteristic curve 0.85 [95% CI, 0.82–0.88] vs 0.71 [95% CI, 0.68–0.75]; p < 0.001). Conclusions: Vital signs more accurately detect cardiac arrest in nonelderly patients compared with elderly patients, which has important implications for how they are used for identifying critically ill patients. More accurate methods for risk stratification of elderly patients are necessary to decrease the occurrence of this devastating event.